Mengembangkan Kreativitas Anak Usia Dini Melalui Kegiatan Pembelajaran Berdiferensiasi Di Kelompok A SPS Negeri Bale Bermain Abdi Praja - Sahlia, Siti; Yuntina, Lily; Rahayu, Wening (Neolectura, 2025)
This study aims to find out how efforts to increase the development of creativity in children in group A through Differentiated Learning Activities and to find out whether Differentiated Learning can develop creativity in children in group A. The research method used in this article is using the Classroom Action Research model. The subjects of this study are 15 children aged 4-5 years. In the research process, research instruments are used. Namely observation and documentation. The subject of this study is SPSN Bale Playing Abdi Praja Group A students with a total of 15 children consisting of 9 boys and 6 girls. The results of the study show that this is shown by an increase in the development of children's creativity from pre-action or pre-cycle, which is 50.3%, increased in Cycle I to 69.66%, and in Cycle II it increased again to 83%. Based on these results, the action study of this class with two cycles was considered successful.